PENERAPAN METODE TALAQQI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL QURAN PESERTA DIDIK PADA MATA PELAJARAN BTQ KELAS VIII DI MADRASAH TSANAWIYAH: PENERAPAN METODE TALAQQI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL QURAN - Annisa Abbas, Rahmi; Syahid, Akhmad; Aidil Sudarmono, Muh; Mustamin; Wahab, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This thesis discusses "The Application of the Talaqqi Method in Improving Students' Quran Reading Skills in the BTQ Subject for Grade VIII at Madrasah Tsanawiyah Yadi Bontocina, Maros Regency." The purpose of this study is to describe the application of the Talaqqi Method in Improving Students' Quran Reading Skills in the BTQ Subject for Grade VIII at Madrasah Tsanawiyah Yadi Bontocina, Maros Regency. This study is a Classroom Action Research (CAR) consisting of two cycles, where each cycle consists of two meetings. The subjects in this study were 30 students in grade VIII at Madrasah Tsanawiyah Yadi Bontocina, Maros Regency. Data collection techniques in this study were observation, interviews, tests, and documentation. The data analysis techniques used in this study were using percentage calculation formulas and average values (mean) for both the analysis of student activity sheet data and the completeness of student learning outcomes. After implementing Talaqqi using two cycles, namely cycle I and cycle II, it can be seen that the reading ability of grade VIII students in the BTQ subject has increased from the pre-cycle to cycle II, which is in accordance with the results of tests conducted by researchers on students during the learning process in class. Where in the pre-cycle, the average score of students was 66.2 (sufficient) with a completion percentage of 33.33%, then in cycle I the average score was 77.4 (good) with a completion percentage of 66.66%, in cycle II the average score was 88.5 (very good) with a completion percentage of 83.33%.